Measurement of irradiation-enhanced creep in nuclear materials : proceedings of an international conference - Cundy, M. R.; Hardt, Peter von der, 1934-; Loelgen, R. H. (EUR (Series), 1977)
Measurement of Irradiation-Enhanced Creep in Nuclear Materials covers the proceedings of an international conference organized by the commission of the European communities. The book presents 37 papers that are organized according to the session of the conference. Each session focuses on various topics that relate to the irradiation creep of a specific material, which are ceramic nuclear fuels, graphite, and non-fissile metal and alloys. The text will be of great use for researchers and professionals whose work involves quantifying irradiation creep in nuclear materials.